(untitled) (Palíndromo, 2020)
This article is a report of my current doctoral research in Artistic Processes, in the research line American Ceramics, in this study a recovery of ancestral knowledge and knowledge that permeates my artistic production, mainly in ceramics. Conceiving a production of objects related to memory, I also bring a relationship with black ancestry, approaching a discussion about issues of African descent, no social context of the state of São Paulo, where I was born and graduated as an artist. These artist’s discoveries in the territory opened possibilities to look at time/space as part of my artistic process and cultural identity